Magic strikes - Andrews, Ilona (New York : Ace Books, 2009)
Drafted into working for the Order of Merciful Aid, Atlanta mercenary Kate Daniels has more paranormal problems than she knows what to do with. But when Kate's werewolf friend Derek is discovered near death, she must confront her greatest challenge yet.
"A Kate Daniels novel"--cover
Keywords: Werewolves; Daniels, Kate (Fictitious character); Fantasy fiction; Fiction